Diagnosis and management of rheumatic manifestations of Hepatitis B, Hepatitis C and immunodeficiency Virus - Arun Ramesh Chogle (Indian Journal of Rheumatology)
Hepatitis B, hepatitis C virus and human immunodeficiency virus infections are important causes of virally mediated arthritis. These can pose several diagnostic and therapeutic dilemmas. This review analyzes the recent publications on this topic and discusses the related issues on diagnosis and treatment.